A review of wine fermentation process modeling. (May 2020) - Miller, Konrad V.; Block, David E.
Abstract: In this work, we review attempts to quantify and model the wine fermentation process. The first part of this review examines yeast fermentation kinetics, from early models of microbial growth to modern genome scale metabolic models. The second part of this review covers physical models of wine fermentors: heat transfer in fermentors, natural convective mixing during fermentation, studies of temperature and concentration gradients in heterogeneous red wine fermentations, and the application of spatial reactor engineering models to wine fermentors, allowing for investigation of the impact of spatial heterogeneity on fermentation dynamics. The third part examines the complex process of phenolic extraction during red winemaking fermentation, which in turn depends on fermentation conditions, such as temperature and ethanol concentration. Finally, we examine some recent work that combines spatial reactor engineering models of wine fermentation dynamics with temperature and ethanol sensitive extraction models, allowing for a new and robust tool in wine fermentation process modeling. Highlights: Wine process modeling elucidates phenomena and allows for process optimization. Fermentation kinetic models describe yeast growth and accumulation of metabolites. Spatial heterogeneity must be modeled in wine fermentations via transport phenomena. Models of wine fermentations should include extraction of phenolics from grapes.